Medical conversion of heart rhythm with amiodarone in patients with atrial fibrillation - A. G. Pronin; A. V. Prokopenko (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2020)
A retrospective study included 93 patients who underwent a drug conversion of the heart rhythm with amiodarone. They were divided into comparison groups. The first group consisted of 58 patients who received monotherapy with amiodarone. The second group consisted of 35 patients in whom propranololol was added to amiodarone. A comparative analysis was conducted to establish the efficacy and safety of medication conversion of rhythm with these treatment options. It was found that atrial fibrillation supplementation with amiodarone in combination with propranololol is registered more frequently and in a shorter time than with amiodarone alone. However, this treatment option is associated with a more pronounced reduction of conductivity in the atrioventricular node and the development of more pronounced bradycardia in 8.6% of cases.